The First-Line Treatment for Advanced Pancreatic Cancer - Merl, Man Yee; Li, Jia; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Pancreatic cancer is sometimes called a "silent killer" because it is often not diagnosed until it is advanced. It remains the fourth leading cause of cancer-related death in the United States. Gemcitabine has been the front line therapy for advanced pancreatic cancer over the past 10 years. Over this time period, survival benefit has not been able to improve substantially from studies of gemcitabine-based combination therapy. A breakthrough to improve treatment options in this setting is needed. In the 2010 ASCO Gastrointestinal Cancers Symposium in Orlando, Florida, USA, several abstracts were presented to explore new agents or combinations as first-line therapy in locally advanced or metastatic settings. In this article, we review and summarize the findings from these studies. Image: Yale-New Haven Hospital. New Haven, CT, USA.